Fine Needle Aspiration Cytology Diagnosis of an Urachal Adenocarcinoma - Thirunavukkarasu, Balamurugan (J Clin Diagn Res, 2016)
Urachal Carcinoma (UC) is a rare malignancy of urinary bladder. It is usually found in adults in advanced stages because the tumour often grows outside the bladder without producing clinical symptoms. Most of the cases are mucinous, intestinal or signet ring cell adenocarcinoma and the diagnosis is usually made on biopsy. Radiographic images of this tumour may show characteristic features with a midline solid or cystic mass in the anterior wall of bladder associated with small calcification, which is considered as a pathognomonic sign for the diagnosis of UC. We report a case of UC in an adult, whose radiographic images suggested an urachal tumour and Fine Needle Aspiration (FNA) cytology revealed an adenocarcinoma. Laparoscopic partial cystectomy with umbilectomy and pelvic node dissection was done without further histopathological confirmation. Surgical intervention of UC on the basis of FNA diagnosis has not been reported in the literature.